Development and Preliminary Evaluation of the RAMAH Pedagogical Model for Internalizing Politeness Values in Child-Friendly Elementary Schools - Maman Johari; Sofyan Sauri; Sofyan Iskandar; Aceng Kosasih (Journal of General Education and Humanities, 2026)
The internalization of politeness remains a challenge in elementary education because existing character education programs are often implemented as fragmented activities rather than coherent pedagogical processes. This study aimed to develop, validate, and evaluate the RAMAH (Respect, Affection, Moderation, Adab, Humanity) Pedagogical Model, implemented through five instructional stages: Reflection, Actualization, Habituation, Affirmation, and Harmonization. An embedded mixed-methods Research and Development design was conducted in two elementary schools implementing the Child-Friendly School Program in Purwakarta Regency, West Java, Indonesia. Participants included school principals, Islamic Religious Education teachers, Child-Friendly School Working Group teachers, three expert validators with expertise in character education, Islamic Religious Education, and elementary education, and 122 elementary school students. Model effectiveness was evaluated using a one-group pretest-posttest design with a paired-samples t-test and N-Gain analysis. The findings indicate that the model demonstrated satisfactory validity and practicality, and that students' politeness-internalization scores increased significantly following its implementation, providing preliminary evidence of effectiveness despite the absence of a control group. The study contributes an integrated pedagogical framework for strengthening politeness internalization within the Child-Friendly School context and provides a foundation for future controlled, longitudinal studies.